Analytical recommendations for SARS-CoV-2 identification by RT-PCR in pediatric patients - Israel Parra-Ortega; Armando Vilchis-Ordoñez; Briceida López-Martínez; Tania Ángeles-Floriano (Permanyer, 2021)
Coronavirus disease 2019 (COVID-19) is caused by the severe acute respiratory syndrome 2 coronavirus (SARS-CoV-2) and is currently listed as a global public health emergency. Timely identification and protocol implementations for molecular detection of this virus are vital for medical decision-making. Identification of SARS-CoV-2 infection cases is based on detection of the virus RNA by molecular tests, particularly real-time reverse transcription-polymerase chain reaction (RT-PCR). Technical and operational details specific to each center must be considered to perform the molecular diagnosis of SARS-CoV-2 in pediatric patients. The term "qualified laboratories" involves laboratories in which all users, analysts, and anyone reporting results are trained to develop and interpret results through a procedure implemented previously by an instructor. Such knowledge is essential in detecting and identifying errors during each of its phases: pre-analytical, analytical, and post-analytical, which allow the establishment of continuous improvement policies to ensure the quality of the results, but above all, the physical integrity of health workers.